The effect of Cerbera odollam leaf and fruit peel extract on subterranean termite Coptotermes curvignathus - Ummahatul Mujahidah; Auliya Ilmiawati; Arinana Arinana; Gustini Syahbirin; Irmanida Batubara (Universitas Lampung, 2026)
Coptotermes curvignathus is a termite pest that attacks buildings, plantations, and forests. Controlling this pest requires environmentally friendly natural materials. The bintaro plant (Cerbera odollam) are known in Indonesia as natural insecticides and traditional medicines because of their strong toxic properties, so they have the potential to be used in termite control. This study evaluated the efficacy of C. odollam leaf and fruit peel extracts as natural termiticides and their effectiveness against subterranean termite C. curvignathus. The extraction process used three solvents with different polarities: n-hexane, acetone, and ethanol. Anti-termite bioactivity tests were conducted following the Japanese Industrial Standard (JIS) 1571-2010 method. Ethanol extract from C. odollam leaves produced the highest yield (9.52%). Phytochemical analysis showed the presence of alkaloids, flavonoids, phenolics, steroids, and saponins in both leaf and fruit peel extracts. The anti-termite bioactivity test showed that the leaf extract with acetone solvent caused 97.33% mortality, while the fruit peel extract with ethanol solvent caused 100% mortality at a 5% concentration. This study demonstrates that C. odollam leaf and fruit peel extracts have strong potential as natural termiticides.